2016
DOI: 10.1021/acs.langmuir.5b03698
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Polystyrene Particles on the Surface of Poly(N-isopropylacrylamide-co-methacrylic acid) Microgels Prepared by Seeded Emulsion Polymerization of Styrene

Abstract: Composite microgels with polystyrene nanoparticles were synthesized by seeded emulsion polymerization of styrene in the presence of pH- and temperature-responsive poly(N-isopropylacrylamide-co-methacrylic acid) microgels as seeds. In particular, the core microgels maintained their swelled state as the pH was increased to 10 during seeded emulsion polymerization conducted at an elevated temperature. Furthermore, we tuned the swelling degree of the core microgels at pH 10 by changing the amount of methacrylic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…Initially, nanocomposite microgels were prepared using poly( N ‐isopropyl acrylamide‐ co ‐methacrylic acid) (NM) microgels, in which the charged groups (carboxyl groups) are localized within the center of the microgels, and styrene (that is, NMS nanocomposite microgels). FE‐SEM and TEM images of ultra‐thin cross sections of the NMS nanocomposite microgels indicated that the deca‐nano sized polystyrene nanoparticles ( D =51±7 nm) were attached to the surface of the NMS microgels (Figure a,b), which is consistent with previous reports . TEM images of the cross‐section revealed highly deformed nanocomposite microgels with no space between the polystyrene nanoparticles (Figure b; Supporting Information, Figure S2).…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…Initially, nanocomposite microgels were prepared using poly( N ‐isopropyl acrylamide‐ co ‐methacrylic acid) (NM) microgels, in which the charged groups (carboxyl groups) are localized within the center of the microgels, and styrene (that is, NMS nanocomposite microgels). FE‐SEM and TEM images of ultra‐thin cross sections of the NMS nanocomposite microgels indicated that the deca‐nano sized polystyrene nanoparticles ( D =51±7 nm) were attached to the surface of the NMS microgels (Figure a,b), which is consistent with previous reports . TEM images of the cross‐section revealed highly deformed nanocomposite microgels with no space between the polystyrene nanoparticles (Figure b; Supporting Information, Figure S2).…”
Section: Figuresupporting
confidence: 89%
“…Here, we used a series of nanocomposite microgels prepared by seeded emulsion polymerization (SEP) of styrene in the presence of microgels as model nanocomposite microgels for cryo‐ET. The nanocomposite morphologies were tuned by controlling the charge distribution inside the microgels or by addition of a surfactant during SEP, as previously reported (see experimental details in the Supporting Information). The obtained 3D images of the various nanocomposite microgels afforded insight into the polymerization process of the nanocomposite microgels and revealed that the hydrophobic styrene monomer is able to recognize molecular‐scale differences in polarity within the microgels during SEP. Based on these results, multilayered nanocomposite microgels were prepared for the first time.…”
Section: Figurementioning
confidence: 99%
“…The size of these microgel particles can be adjusted by tuning the solvent composition, degree of crosslinking, addition of ionic surfactant in the reaction mixture, reaction temperature, initiator concentration, and monomer/comonomer ratio. Various comonomers such as acrylic acid (AA), methacrylic acid (MAA), vinyl imidazole (Vim), aminoethyl methacrylate hydrochloride (AEMA), polymer chains, and metal nanoparticles have also been incorporated inside these microgels during synthesis or via postmodification for various applications ( Scheme ) …”
Section: Methods For Designing Functional Microgelsmentioning
confidence: 99%
“…When performing the polymerization of styrene in the swollen state (under appropriate pH-conditions), the PS-particles are found to form a non-compact surface layer. Under pH-induced deswelling, this layer does not become more compact, but NPs seem to diffuse inside the microgel [73]. Finally, in a very recent contribution on the same subject, the Suzuki group presented seeded polymerization of styrene in presence of microgels below the volume phase transition temperature [74].…”
Section: The Route To Stimuli-responsive Multi-domain Structuresmentioning
confidence: 99%
“…The tuning of the localisation of in-microgel generated nanoparticles has been promoted by Suzuki's group in the past years to design new types of thermoresponsive particles, with thermoresponsive microgels of poly(N-isopropylacrylamide) cross-linked with N,N′-methylene-bis-acrylamide as cores or seeds for the polymerisation which are surrounded by a hard polystyrene shell [72][73][74]. Following a seeded emulsion protocol in the presence of p(NIPAM) microgel particles, the PS particles where found to form raspberry-like structures under high temperature, surfactant-free polymerisation, with however some remaining thermosensitivity, presumably due to incomplete coverage by PS [72].…”
Section: The Route To Stimuli-responsive Multi-domain Structuresmentioning
confidence: 99%